2013
DOI: 10.1007/s00264-013-1796-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative properties and surface damage mechanisms of remelted highly crosslinked polyethylenes in total knee arthroplasty

Abstract: Purpose Remelted highly crosslinked polyethylenes (HXLPEs) were introduced in total knee replacement (TKR) starting in 2001 to reduce wear and particle-induced lysis. The purpose of this study was to investigate the damage mechanisms and oxidative stability of remelted HXLPEs used in TKR. Methods A total of 186 posteriorly stabilised tibial components were retrieved at consecutive revision operations. Sixty nine components were identified as remelted HXLPE. The conventional inserts were implanted for 3.4±2.7 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…In the other cases, namely remelted HXLPE subjected to aging alone, or to aging and cyclic loading, comparatively lower OIs were registered. Our results generally agree with previous retrieval studies that confirmed ex vivo stability loss and measurable oxidation levels for remelted HXLPE explants [9,15,16,22,24]. In this sense, Oral and colleagues recently demonstrated that absorbed squalene, a biological prooxidant, could initiate and accelerate oxidation in remelted crosslinked polyethylene [24].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the other cases, namely remelted HXLPE subjected to aging alone, or to aging and cyclic loading, comparatively lower OIs were registered. Our results generally agree with previous retrieval studies that confirmed ex vivo stability loss and measurable oxidation levels for remelted HXLPE explants [9,15,16,22,24]. In this sense, Oral and colleagues recently demonstrated that absorbed squalene, a biological prooxidant, could initiate and accelerate oxidation in remelted crosslinked polyethylene [24].…”
Section: Discussionsupporting
confidence: 92%
“…In their study, although all retrievals showed minimal oxidation at explantation, oxidation was observed to increase during shelf storage and long-term exposure of the retrievals to air. Likewise, other retrieval programs have reported evidence of measurable oxidation levels in remelted HXLPE retrievals after short or intermediate implantation times [8,9,16]. The mechanism of in vivo oxidation for remelted HXLPEs remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…To decrease the potential for oxidative degradation, heating the polymer to above its melting point (''remelting'') or to just below that temperature (''below-melt thermal annealing'') is a step added postirradiation to reduce the free radicals. However, retrieved crosslinked PE tibial inserts demonstrate increased oxidation levels at the articular surfaces after in vivo implantation regardless of whether they were either remelted or annealed after crosslinking, a phenomenon not observed with pristine, never implanted inserts [13,14,25].…”
Section: Introductionmentioning
confidence: 88%
“…For example, the reduced fracture toughness in XLPE is a cause for concern in tibial post fractures in posterior-stabilized TKAs [30]. Evaluation of surface damage and oxidative properties of retrieved XLPE TKA tibial components from revision surgeries showed little improvement with the use of XLPE [20,27]. The first retrieval analysis of XLPE tibial inserts used an optical grading method to analyze surface damage and found no differences between eight XLPE tibial inserts and 71 conventional PE inserts [23].…”
Section: Introductionmentioning
confidence: 99%